TINGKAT TUTUR BAHASA JEPANG DAN BAHASA JAWA: ANALISIS KONTRASTIF - Eman Suherman (Humaniora, 2009)
In Japanese speech levels, a polite form is known as Keego, which consists of Sonkeego, Kenjoogo, and Teeneego. In Javanese, such a form is called Unda-Usuk. It consists of Ngoko (divided into Ngoko Lugu, Antya Basa, and Basa Antya), Madya (divided into Madya Ngoko, Madyantara, and Madya Krama), and Krama (divided into Mudha Krama, Kramantara, and Wreda Krama). Based on the results of the contrastive analysis used in this paper, it was found out that there are similararities as well as differences between Keego and Unda-Usuk. Both of them have honorific forms as well as humble forms. The difference is that in Japanese there are two concepts known as Uchi and Soto. This means that Japanese pay attention to who a speaker is talking to and who is being discussed. Another difference is that Ngoko can not be contrasted with Keego. Krama Inggil and Krama Andhap do not belong to speech levels. Both are lexicons giving varieties to the existing speech levels, whereas Sonkeego and Kenjoogo are parts of Keego.